Cell-type-Specific Patterned Stimulus-Independent Neuronal Activity in the Drosophila Visual System during Synapse Formation. - Akin, O.; Bajar, B.T.; Keles, M.F.; Frye, M.A.; Zipursky, S.L. (Neuron, 2019)
Stereotyped synaptic connections define the neural circuits of the brain. In vertebrates, stimulus-independent activity contributes to neural circuit formation. It is unknown whether this type of activity is a general feature of nervous system development. Here, we report patterned, stimulus-independent neural activity in the Drosophila visual system during synaptogenesis. Using in vivo calcium, voltage, and glutamate imaging, we found that all neurons participate in this spontaneous activity, which is characterized by brain-wide periodic active and silent phases. Glia are active in a complementary pattern. Each of the 15 of over 100 specific neuron types in the fly visual system examined exhibited a unique activity signature. The activity of neurons that are synaptic partners in the adult was highly correlated during development. We propose that this cell-type-specific activity coordinates the development of the functional circuitry of the adult brain.